Elastyczność organizacji - perspektywa zdolności dynamicznych - Stańczyk-Hugiet, Ewa (Flexible Organization - Dynamic Capabilities' Perspective, 2008)
The paper generally presents learning organization concept. Attention is focused not on learning organization concept but on the exploitation options of that concept in strategic management. Especially when organizations operate in dynamic environment the speed of operations seems to be important but also important is flexibility of operations. It seems that organizational learning processes increase organization's flexibility potential.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 349-356